Cambodia : Second Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Performance under the first year of Cambodia's Poverty Reduction Growth Facility (PRGF)-supported program was strong, with a resumption of growth, low inflation, and significant progress in major areas of structural reform. External developments have reflected increased garment exports and tourism earnings, sharply higher oil imports, and higher capital inflows. The IMF staff urges the authorities to make effective use of planned technical assistance under the Technical Cooperation Action Plan. Structural reforms for 2001 will focus on those areas critical for achieving the macroeconomic objectives.